Exchange Regime Choice with Multinomial Panel Data: Case of the North Africa Countries - Hassan, Esmak; Zakaria, Firano (International Journal of Economics and Financial Issues, 2014)
The objective of this paper is to identify the determinants of exchange regime choice for North Africa Region. The target is to provide an empirical framework suitable for describe and determine the factors having a significant influence on the development of the choice of the regime of exchange. The empirical approach is based on a model of multinomial probit with panel data. The choice of this new approach is justified by the need for collecting the dynamics of the choice of exchange regime, without having recourse to an orthodoxy design (binomial), and by collecting individual heterogeneity between the various countries of the panel. The results obtained affirm that the financial development, the economic growth and monetary creation constitute the principal determinants of exchange regime. Other variables are also significant; it acts in particular of the level of the foreign debt, the inflation and the rate of opening. As, the results affirm as the fixed regimes of the countries of the panel are largely explained by the dependence to external flows and of the importance of monetary reserves in the design of exchange and monetary policies. Being dependent on the exogenous creation of the currency, the worldwide choose a fixed regime of exchange by drawing more and more interventionism on the level of the exchange market. Keywords: Exchange rate regime; multinomial panel data; economics growth. JEL Classifications: E42; F41